Aortic injury repair in a patient with situs inversus totalis and dextrocardia. Issue 4 (15th April 2022) - Ishimine, Tohru; Ishigami, Takahiro; Chida, Kohei; Taniguchi, Naoki; Tengan, Toshiho; Mototake, Hidemitsu
Abstract: Situs inversus totalis (SIT) with dextrocardia is a rare autosomal recessive disorder. We herein describe a blunt thoracic aortic injury (BTAI) in a patient with SIT and dextrocardia. An 18-year-old girl who was injured by a fall presented to our hospital. Computed tomography (CT) revealed a traumatic pseudoaneurysm at the aortic isthmus. Open aortic repair was performed through a right thoracotomy. No abnormal findings were observed on CT 1 year after the surgery. Open aortic repair of BTAI can be safely performed through a right thoracotomy in patients with SIT and dextrocardia.